BIBLIOMETRIC INSIGHTS INTO EARNINGS MANAGEMENT: TRENDS AND FUTURE DIRECTIONS - Irmawati, Irmawati; Rasyid, Syarifuddin; Syamsuddin, Syamsuddin (Jurnal Aplikasi Akuntansi, 2025)
This study presents a bibliometric analysis of earnings management research over 1994–2024, exploring trends, key contributors, and future directions. Using Scopus as the primary database, 1,481 studies were analyzed through VOSviewer and Biblioshiny R to map collaborations, co-citation networks, and thematic evolutions. The findings reveal a 17.79% annual growth rate, with central themes such as corporate governance, discretionary accruals, and audit quality remaining pivotal. Emerging topics, including ESG integration, gender diversity, and the impact of COVID-19, demonstrate the field’s adaptability to contemporary challenges. Future research should explore advanced technologies like AI and blockchain, global regulatory harmonization, and the long-term impacts of real earnings management. The study’s novelty lies in its integrative approach, providing a decade-spanning thematic analysis and bridging traditional concepts with modern challenges. This framework serves as a valuable resource for academics, practitioners, and policymakers addressing financial reporting complexities in a globalized economy.